Systematic Construction of Criminal Policy in the Defense Industry Law Partially Amended by the Job Creation Law - Akhyar, Wira Iqomudin; Deksino, G. Royke; Jupriyanto, Jupriyanto (Reformasi Hukum, 2024)
Criminal law issues strengthen the commonly used administrative law policies. However, the systematic construction of criminal provisions in a law has the potential to "disturb" the implementation process. This article analyzes the systematic construction of criminal provisions in Law No. 16 of 2012 concerning the Defense Industry, partially amended by Law No. 6 of 2023 concerning Job Creation. Qualitative research methods describe legal issues regarding criminal provisions using a normative juridical approach. The results found were that the systematic construction of the criminal provisions in a quo law was separate between the prohibition chapter and the formulation of the criminal offense. The addition of certain legal subjects has the juridical consequence of adding criminal articles to the Job Creation Law. The suggestion proposed is consistency in the formulation of the main article with the prohibition chapter.